1998
DOI: 10.1016/s0029-7844(97)00680-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of placental cytokine-producing cells in term and preterm labor

Abstract: The source of labor-associated release of tumor-necrosis-factor-alpha from placental tissues are macrophages, whereas interleukin-1beta and interleukin-6 are released from placental endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 22 publications
6
35
1
6
Order By: Relevance
“…25,34 Previous studies have shown placental production of cytokines such as IL-1β and adiponectin in normal pregnancy. 8,9,27 In the present study, pregnant women with GDM showed at second trimester (a period of insulin resistance development) higher insulin resistance compared to BMI-and age-matched pregnant women without GDM. Furthermore, pregnant women with GDM presented at 2 nd trimester lower serum adiponectin and higher IL-1β levels than women without GDM.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…25,34 Previous studies have shown placental production of cytokines such as IL-1β and adiponectin in normal pregnancy. 8,9,27 In the present study, pregnant women with GDM showed at second trimester (a period of insulin resistance development) higher insulin resistance compared to BMI-and age-matched pregnant women without GDM. Furthermore, pregnant women with GDM presented at 2 nd trimester lower serum adiponectin and higher IL-1β levels than women without GDM.…”
Section: Discussionsupporting
confidence: 49%
“…40,41 Otherwise, the significant decrease of the studied cytokines during the early postpartum period in pregnancies with GDM in this study could be explained by the withdrawal of cytokines produced by the placenta during pregnancy. 8,9,27 The role of the placenta in the production of adiponectin and IL-1β during pregnancy is further reinforced by the non-significant but clear downward trend of these cytokines during third day postpartum found in pregnancies without GDM. The 3 rd day postpartum is a period in which the effect of the placenta on maternal metabolism regarding insulin resistance has just been removed and lactation is started.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism through which epidural analgesia may trigger cytokine production during labor is not clear. However, the placenta is a rich source of cytokine production, 14 which may explain the unique response to epidural analgesia observed during labor. Increased placental inflammation has been reported in the setting of epidural fever, 15 supporting the placenta as a potential source.…”
Section: Commentmentioning
confidence: 99%
“…Placental cytokine production occurs predominantly from resident macrophages (24), the trophoblast (25), and endothelial cells. This system is partially regulated by glucocorticoids via transcriptional regulation of cytokine genes (26,27).…”
mentioning
confidence: 99%